Hysteroscopy today: is it yet a conventional diagnostic technique in abnormal uterine bleeding? - Vithal, Aditi; Nakum, Kanaklata; Patel, Disha; Patel, Juhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To assess the efficacy of hysteroscopy over dilatation and curettage in diagnosis of abnormal uterine bleeding. Methods: A total of 51 women in reproductive and peri- menopausal age group (19-55 years) with complaints of abnormal uterine bleeding were enrolled in the study. All the patients underwent hysteroscopic examination followed by D&C/histopathological evaluation. Hysteroscopic findings were compared against histopathological findings. Results: Majority of patients belonged to 36-40 years of age group. Majority (40%) presented within 6 months of complaints. Hysteroscopically, 46% had abnormal findings 12% had cervical polyps, 12% fibroid polyps, 18% endometrial polyps, 2% had adhesions (Ashermann’s syndrome) and 2% had a forgotten intrauterine contraceptive device. On histopathology (D&C) 64% cases had normal/proliferative/atrophic endometrium, 12% had hyperplasia and 6% had polyp. Conclusions: Hysteroscopy provided additional information for some of the pathologies which would otherwise be undiagnosed by HPE.